Evaluating community competence of Barangay Balinacon, Nagcarlan, Laguna - Abad, Yahwe Keyan G.; Amancio, Ma. Jenie Ruth H.; Aromin, Paula Benilda C.; Gaspar, Aldin D.; Isidro, Pocholo N.; Lejarde, Julius G.; Lim Reymund Jay L.; Maniego, Ma. Christianne R.; Medina, Kristine Marie D.
The concept of conducting evaluative studies in the health sector have risen from the need to determine the efficiency of health programs in terms of focus of action and delivery of ervices. This research aims to provide a qualitative and descriptive evaluation of the community competence of Barangay Balinacon in terms of impact, process and outcome indicators for the problems on waste management, diabetes, hypertension, lifestyle, and parasitism, as well as the proficiency of the supervisees and core group members as leader, health service provider, and health educator after 4 years of entry of student nurses in the community. Several evaluation tools were constructed in replication of and utilized from a previous study of Abaca et. al (2006).